La situation en Hongrie (fin). Rapport spécial du Comité spécial pour la question de Hongrie (fin). Séance Plénière 787e, Treizième session , Point 69 de l'ordre du jour . The Situation in Hungary (Concluded). Special Report of the Special Committee on the Problem of Hungary (Concluded). Plenary Meeting 787th, Thirteenth Session , Agenda Item 69 - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly The same as 25-85-1-8 in French.